2022
DOI: 10.1186/s13287-022-02787-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of off-the-shelf hematopoietic stem cell-engineered invariant natural killer T cells for COVID-19 therapeutic intervention

Abstract: Background New COVID-19 treatments are desperately needed as case numbers continue to rise and emergent strains threaten vaccine efficacy. Cell therapy has revolutionized cancer treatment and holds much promise in combatting infectious disease, including COVID-19. Invariant natural killer T (iNKT) cells are a rare subset of T cells with potent antiviral and immunoregulatory functions and an excellent safety profile. Current iNKT cell strategies are hindered by the extremely low presence of iNKT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 98 publications
2
37
0
Order By: Relevance
“…The cell product harvested from transduced BLT mice displayed a significant increase in the HSC-iNKT population, and their anti-tumor capacity was confirmed against an MM.1S human multiple myeloma cell line using in vitro and in vivo models. However, to produce a more massively scalable platform for HSC-iNKT generation, a modified ex vivo artificial thymic organoid (ATO) culture system was designed to grow HSCs [ 18 , 19 ]. While the ATO platform was designed for the in vitro generation of conventional T cells from HSCs using a 3D stromal cell matrix, iNKT TCR transduction combined with αGC stimulation successfully produced a high-yield and high-purity HSC-iNKT cell product [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cell product harvested from transduced BLT mice displayed a significant increase in the HSC-iNKT population, and their anti-tumor capacity was confirmed against an MM.1S human multiple myeloma cell line using in vitro and in vivo models. However, to produce a more massively scalable platform for HSC-iNKT generation, a modified ex vivo artificial thymic organoid (ATO) culture system was designed to grow HSCs [ 18 , 19 ]. While the ATO platform was designed for the in vitro generation of conventional T cells from HSCs using a 3D stromal cell matrix, iNKT TCR transduction combined with αGC stimulation successfully produced a high-yield and high-purity HSC-iNKT cell product [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to produce a more massively scalable platform for HSC-iNKT generation, a modified ex vivo artificial thymic organoid (ATO) culture system was designed to grow HSCs [ 18 , 19 ]. While the ATO platform was designed for the in vitro generation of conventional T cells from HSCs using a 3D stromal cell matrix, iNKT TCR transduction combined with αGC stimulation successfully produced a high-yield and high-purity HSC-iNKT cell product [ 18 , 19 ]. These cells retained proper iNKT morphology and functional profile, showing significant anti-tumor capacity against multiple human solid tumor cell lines [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified that innate T cells, such as iNKT cells, can remediate immunosuppression through the targeting of anti-inflammatory TAMs [ 23 ]. Therefore, this study seeks to examine the efficacy of MAIT, iNKT, and γδT cells in targeting alternatively activated macrophages in vitro, and to assess their application in CAR therapies.…”
Section: Introductionmentioning
confidence: 99%